SNHG10 Is a Prognostic Biomarker Correlated With Immune Infiltrates in Prostate Cancer - Chen, Qiang; Yang, Xiaorong; Gong, Binbin; Xie, Wenjie; Ma, Ming; Fu, Shengqiang; Wang, Siyuan; Liu, Yutang; Zhang, Zhicheng; Sun, Ting; Li, Zhilong (Frontiers in Cell and Developmental Biology, 2021)
SNHG10 is a long non-coding RNA (lncRNA) found to be overexpressed in multiple human cancers including prostate cancer (PC). However, the underlying mechanisms of SNHG10 driving the progression of PC remains unclear. In this study, we investigated the role of SNHG10 in PC and found that SNHG10 expression was significantly increased in datasets extracted from The Cancer Genome Atlas. Increased expression of SNHG10 was related to advanced clinical parameters. Receiver operating curve analysis revealed the significant diagnostic ability of SNHG10 (AUC = 0.805). In addition, immune infiltration analysis, and GSEA showed that SNHG10 expression was correlated with oxidative phosphorylation and immune infiltrated cells. Finally, we determined that SNHG10 regulated cell proliferation, migration, and invasion of PC in vitro. In conclusion, our data demonstrated that SNHG10 was correlated with progression and immune infiltration, and could serve as a prognostic biomarker for PC.